Fishing ground and tuna productivity by tuna longline based on Benoa Bay, Bali, Indonesia - Mohammad Imron; MUHAMMAD IRSYAD TAWAQAL; ROZA YUSFIANDAYANI (Society for Indonesian Biodiversity, 2021)
Abstract. Imron M, Tawaqal MI, Yusfiandayani R. 2021. Fishing ground and tuna productivity by tuna longline based on Benoa Bay, Bali, Indonesia. Biodiversitas 22: 961-968. The success of a longline fishing operation depends on several things such as the skill of the crew, bait used, fishing season, fishing operation, the total of fish caught, the price of the fish, productivity, and fishing grounds. Information about productivity and fishing ground becomes important to increase effectiveness and optimal profit. The methodology is carried out by conducting a survey to collect data to be processed and analyzed using productivity analysis based on Landing per Unit Effort (LPUE) and fishing activity analysis from the Vessel Monitoring System (VMS) to determine the Fishing Ground. We calculate tuna productivity from catch production (landing) per effort, meanwhile fishing ground use VMS data. Production tuna was landed at Benoa Bali from 2016-2018 fluctuated. In 2016 production of tuna albacore took a portion of 34.60%, yellowfin tuna 43.56%, bigeye tuna 15.44%, and southern bluefin tuna 6.26%. Production of tuna albacore took a portion of 35.61%, yellowfin tuna 42.64%, bigeye tuna 12.49%, and southern bluefin tuna 9.26% in 2017. Production albacore took a portion of 36.41%, yellowfin tuna 41.56%, bigeye tuna 11.79%, and southern bluefin tuna 10.24% in 2018. The highest productivity of albacore was in August 2018 with LPUE value 1.0099, yellowfin tuna was in July 2018 with LPUE value 1.2431, big eye tuna was in November 2018 with LPUE value 0.5538, and bluefin was at December 2017 with LPUE value 0.3864. The result of VMS data processing showed that tuna longline vessel based at Benoa has several locations of fishing grounds based on fishing activity for example Hindia High Seas, WPP NRI 714 (Telo gulf and Banda Sea), WPP NRI 718 (Aru Sea, Arafura Sea, and Timor Sea), ZEEI WPP NRI 718.